Role of amino acids and peptides in the molecular signaling in skeletal muscle after resistance exercise - Koopman, R. (International Journal of Sport Nutrition and Exercise Metabolism, 2007)
Resistance exercise can effectively result in an increase in muscle mass, or hypertrophy, which generally becomes apparent after several weeks of training. Muscle hypertrophy requires muscle protein synthesis to exceed protein breakdown during an extended time period. It has been firmly established that the interaction between exercise and nutrition (i.e., protein intake) is necessary to attain net protein accretion in skeletal muscle. The stimulation of protein synthesis is caused in part by stimulation of mRNA translation initiation. There is relatively little information on the response of intracellular signaling controlling mRNA translation to exercise and nutrition, especially in humans, but the available data in humans seem to suggest that a single bout of resistance exercise does not substantially enhance PI-3 kinase/mTOR signaling during the first 2 h after exercise. Moreover, it is demonstrated that the ingestion of protein or amino acids after exercise is crucial to further stimulate molecular signaling that controls translation initiation. The aim of this review is to provide an overview of the intracellular signaling related to translational control and to provide a summary of the current knowledge about the response of the signaling pathways controlling the anabolic response to exercise and nutrient intake in vivo in humans.